2008
DOI: 10.1016/j.aorn.2007.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Adolescents for Outpatient Surgery: Using an Internet Program

Abstract: This study compared the effectiveness of an Internet-based method with a standard method for preparing adolescent patients scheduled for out-patient tonsillectomy procedures. A two-group experimental design compared adolescents' state anxiety, knowledge acquisition, postoperative pain intensity, and satisfaction with the method of preoperative preparation. Parents' state anxiety and satisfaction with their child's preparation method also were compared. Data analysis revealed significantly increased knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 44 publications
(60 reference statements)
0
47
0
4
Order By: Relevance
“…Internet-based systems are flexible communication methods that deliver the latest, most up-to-date information [32], and their use for pain management has become popular [33]. Previous studies using Internet-based learning programs have reported reduced pain [34–36], facilitated knowledge acquisition [37], facilitated self-care education [38], and improved health status [39]. However, the effects of auricular acupressure combined with Internet-based programs on menstrual pain and self-care for dysmenorrheic adolescents may be more comprehensive.…”
Section: Introductionmentioning
confidence: 99%
“…Internet-based systems are flexible communication methods that deliver the latest, most up-to-date information [32], and their use for pain management has become popular [33]. Previous studies using Internet-based learning programs have reported reduced pain [34–36], facilitated knowledge acquisition [37], facilitated self-care education [38], and improved health status [39]. However, the effects of auricular acupressure combined with Internet-based programs on menstrual pain and self-care for dysmenorrheic adolescents may be more comprehensive.…”
Section: Introductionmentioning
confidence: 99%
“…16 Parents of the Internet-prepared adolescents also reported greater satisfaction (P 5 .004) than parents of the standard-prepared and nontreatment groups. There were no statistically significant differences among the three groups on adolescent or parental anxiety or adolescent postoperative pain intensity.…”
Section: Preoperative Education For Pediatric Surgerymentioning
confidence: 90%
“…4,10, [16][17][18][19][20][21][22] Outcome measures tested included knowledge retention, anxiety, and effectiveness of NPs in the presurgical clinic as well as satisfaction with the process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As high levels of pain are associated with the anxiety and fear level of the patient, providing education is one of the most important strategies that can be used by the nurse for reducing postoperative pain [21]. Research has demonstrated that anxiety levels of the patient and his/her family, and the information required by each, are comparable [22,23]. Anxieties of patients in general have been found to be associated with lack of information.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Educational programs designed according to the needs of patients also are found to help satisfy the patient's need for knowledge, to decrease anxiety, to shorten the discharge time, and to allow discharge with less cost [22,26,27].…”
Section: Introductionmentioning
confidence: 99%